Correlation between the surface characteristics of carbon supports and their electrochemical stability and performance in fuel cell cathodes. Issue 4 (31st March 2021) - Jiménez‐Morales, Ignacio; Reyes‐Carmona, Alvaro; Dupont, Marc; Cavaliere, Sara; Rodlert, Marlene; Mornaghini, Flavio; Larsen, Mikkel J.; Odgaard, Madeleine; Zajac, Jerzy; Jones, Deborah J.; Rozière, Jacques
Abstract: In this paper, an extensive characterisation of a range of carbon blacks (CB) with similar surface area but different surface chemistry is carried out by flow calorimetry, Raman spectroscopy, dynamic water vapour sorption, instrumental gas analysis, nitrogen adsorption/desorption and high potential chronoamperometry. Using these carbon materials as supports, Pt/CB electrocatalysts are prepared by microwave‐assisted polyol‐mediated synthesis in gram scale. Structural, morphological and electrochemical properties of the prepared electrocatalysts are evaluated by X‐ray diffraction, transmission electron microscopy, rotating disc electrode and in situ fuel cell characterisation of the corresponding membrane–electrode assemblies. The obtained results allow to establish a relationship between surface chemistry and electrochemical properties useful for the design of Pt/C catalyst layers with high performance and stability. Abstract : Surface properties of carbon supports play a role in the electrochemical and durability characteristics of the corresponding electrocatalysts and catalyst layers: cathodes based on carbon blacks with hydrophobic character demonstrated improved oxygen reduction reaction activity, durability and mass transfer.